Fasting Ketonuria and the Risk of Incident Nonalcoholic Fatty Liver Disease With and Without Liver Fibrosis in Nondiabetic Adults. (11th November 2021) - Kim, Yejin; Chang, Yoosoo; Kwon, Min-Jung; Hong, Yun Soo; Kim, Mi Kyung; Sohn, Won; Cho, Yong Kyun; Shin, Hocheol; Wild, Sarah H.; Byrne, Christopher D.; Ryu, Seungho
Abstract : INTRODUCTION: Dietary carbohydrate restriction or ketogenic diets are known to be beneficial in preventing liver fat accumulation. However, the effect of ketonemia on the risk of nonalcoholic fatty liver disease (NAFLD) in nondiabetic population is largely unknown. We investigated the association between fasting ketonuria and the risk of incident NAFLD in healthy adults. METHODS: A cohort of 153, 076 nondiabetic Koreans with no hepatic steatosis and low probability of fibrosis at baseline was followed for a median of 4.1 years. The outcome was incident hepatic steatosis with or without liver fibrosis, and it was assessed by liver ultrasound and noninvasive fibrosis indices, including fibrosis-4 and the NAFLD fibrosis score (NFS). Parametric proportional hazard models were used to estimate hazard ratios (HRs) for outcome according to ketonuria status. RESULTS: Within 677, 702.1 person-years of follow-up, 31, 079 subjects developed hepatic steatosis. Compared with no ketonuria (reference), fasting ketonuria was significantly associated with a decreased risk of incident hepatic steatosis, with multivariable-adjusted HRs (95% confidence interval) of 0.81 (0.78–0.84). The corresponding HRs for incident hepatic steatosis with intermediate-to-high NFS were 0.79 (0.69–0.90). Similar associations were observed replacing NFS with fibrosis-4. In addition, the presence of persistent ketonuria at both baseline and subsequent visit was associated with the greatest decrease in the adjusted HR for incident NAFLD. DISCUSSION: Ketonuria was associated with a reduced risk of developing incident hepatic steatosis with and without intermediate-to-high probability of advanced fibrosis in a large cohort of nondiabetic healthy individuals. The role of hyperketonemia in the prevention of NAFLD requires further exploration.